1994
DOI: 10.1002/em.2850230310
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis testing in Drosophila. X. Results of 70 coded chemicals tested for the national toxicology‐program

Abstract: Seventy chemicals were tested for the ability to induce sex-linked recessive lethal (SLRL) mutations in postmeiotic and meiotic germ cells of male Drosophila melanogaster. As in the previous studies in this series, adult feeding was chosen as the first route of administration. If the compound failed to induce mutations by this route, injection exposure was used. Two chemicals, n-butane and propylene, were gaseous and therefore tested only by inhalation. One chemical (dimethylcarbamoyl chloride) was tested only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…However, data on solubility in ethanol are lacking for (JECFA, 1998b;JECFA, 2000d) (Simmon and Shephard, 1981) Gene mutation S. typhimurium TA98, TA100, TA1537 not reported 1 negative (Nagao and Takahashi, 1981) Gene mutation S. typhimurium TA98, TA100, TA1535, TA1537, TA1538 10-10 000 µg/plate 1 negative (Richold and Jones, 1981) Gene mutation S. typhimurium TA98, TA100 500 -1000 µg/ml negative (Ichinotsubo et al, 1981a) Fluctuation Test S. typhimurium TA98, TA100 500 µg/ml 1 negative (Hubbard et al, 1981) Forward mutation S. typhimurium TM677 1000 µg/ml 2 negative (Skopeck et al, 1981) Microtiter fluctuation S. typhimurium TA98, TA1535, TA1537 10-1000 µg/ml 1 negative (Gatehouse, 1981) Gene mutation E. coli 500 µg/plate 1 negative (Venitt and Crofton-Sleigh, 1981) Gene mutation E. coli SA500 250 µg/plate lethal (Dambly et al, 1981) Differential killing test E. coli WP2, WP67 & M871 2500 µg/plate 1 negative (Green, 1981) Differential killing assay E. coli P2,WP67 & CM871 1000 µg/ml 1 negative (Tweats, 1981) Microtiter fluctuation E. coli WP2 uvrA 10-1000 µg/ml 1 negative (Gatehouse, 1981) Gene mutation E. coli WP2 uvrA pKM102 not reported 1 negative (Matsushima et al, 1981) Sister chromatid exchange Chinese hamster ovary cells 148-1480 µg/ml (Kada, 1981) Unscheduled DNA synthesis Human HeLa S3 cells 0.1-100 µg/ml 1 negative (Martin and McDermid, 1981) Mitotic gene conversion S. cerevisiae 750 µg/ml 1 negative (Sharp and Parry, 1981) Clastogenic activity Rat liver cell line RL1 250 µg/ml negative (Dean, 1981) Mammalian cell transformation BHK21C1B/HRC1 cells 2500 µg/ml 1 ? 5 (Daniel and Dehnel, 1981) Mammalian cell transformation BHK-21 hamster kidney cells 250 µg/ml 2 positive (Styles, 1981) Degranulation assay Rat 25 mg/ml positive (Fey et al, 1981) Cell growth inhibition S. cerevisiae 750 µg/ml 1 negative (Sharp and Parry, 1981) (Rosenkranz et al, 1981) Sperm head abnormality (CBA x Balb/c)F 1 mice 0.1-1.0 mg/kg/ day ip (5 days) negative (Topham, 1981) Sex-linked recessive test Drosophila melanogaster 20 000 or 28 000 mg/ kg (diet) or 15 000 mg/kg (injection) negative (Foureman et al, 1994) Micronucleus test B6C3F 1 mice 0.7 mg/kg/day ip (2 days) negative Micro...…”
Section: Resultsmentioning
confidence: 99%
“…However, data on solubility in ethanol are lacking for (JECFA, 1998b;JECFA, 2000d) (Simmon and Shephard, 1981) Gene mutation S. typhimurium TA98, TA100, TA1537 not reported 1 negative (Nagao and Takahashi, 1981) Gene mutation S. typhimurium TA98, TA100, TA1535, TA1537, TA1538 10-10 000 µg/plate 1 negative (Richold and Jones, 1981) Gene mutation S. typhimurium TA98, TA100 500 -1000 µg/ml negative (Ichinotsubo et al, 1981a) Fluctuation Test S. typhimurium TA98, TA100 500 µg/ml 1 negative (Hubbard et al, 1981) Forward mutation S. typhimurium TM677 1000 µg/ml 2 negative (Skopeck et al, 1981) Microtiter fluctuation S. typhimurium TA98, TA1535, TA1537 10-1000 µg/ml 1 negative (Gatehouse, 1981) Gene mutation E. coli 500 µg/plate 1 negative (Venitt and Crofton-Sleigh, 1981) Gene mutation E. coli SA500 250 µg/plate lethal (Dambly et al, 1981) Differential killing test E. coli WP2, WP67 & M871 2500 µg/plate 1 negative (Green, 1981) Differential killing assay E. coli P2,WP67 & CM871 1000 µg/ml 1 negative (Tweats, 1981) Microtiter fluctuation E. coli WP2 uvrA 10-1000 µg/ml 1 negative (Gatehouse, 1981) Gene mutation E. coli WP2 uvrA pKM102 not reported 1 negative (Matsushima et al, 1981) Sister chromatid exchange Chinese hamster ovary cells 148-1480 µg/ml (Kada, 1981) Unscheduled DNA synthesis Human HeLa S3 cells 0.1-100 µg/ml 1 negative (Martin and McDermid, 1981) Mitotic gene conversion S. cerevisiae 750 µg/ml 1 negative (Sharp and Parry, 1981) Clastogenic activity Rat liver cell line RL1 250 µg/ml negative (Dean, 1981) Mammalian cell transformation BHK21C1B/HRC1 cells 2500 µg/ml 1 ? 5 (Daniel and Dehnel, 1981) Mammalian cell transformation BHK-21 hamster kidney cells 250 µg/ml 2 positive (Styles, 1981) Degranulation assay Rat 25 mg/ml positive (Fey et al, 1981) Cell growth inhibition S. cerevisiae 750 µg/ml 1 negative (Sharp and Parry, 1981) (Rosenkranz et al, 1981) Sperm head abnormality (CBA x Balb/c)F 1 mice 0.1-1.0 mg/kg/ day ip (5 days) negative (Topham, 1981) Sex-linked recessive test Drosophila melanogaster 20 000 or 28 000 mg/ kg (diet) or 15 000 mg/kg (injection) negative (Foureman et al, 1994) Micronucleus test B6C3F 1 mice 0.7 mg/kg/day ip (2 days) negative Micro...…”
Section: Resultsmentioning
confidence: 99%
“…When cyclohexanone ] was fed to adult Drosophila melanogaster for 3 days, no mutations were observed (Goncharova, 1970;Wild et al, 1983;Foureman et al, 1994). In addition, negative results were obtained when D. melanogaster were injected with a single dose of 12 500 µg of isophorone (Foureman et al, 1994).…”
Section: In Vivomentioning
confidence: 99%
“…In addition, negative results were obtained when D. melanogaster were injected with a single dose of 12 500 µg of isophorone (Foureman et al, 1994).…”
Section: In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings [33][34][35][36] , especially using Ames test [33][34]36) , need consideration. While many studies found positive Ames tests with MDI and TDI, these used DMSO (dimethylsulfoxid) or other solvents to disperse the diisocyanates into the medium.…”
Section: Mutagenicitymentioning
confidence: 99%